A comparative study on the accuracy of SRK/T, holladay II, and barrett universal II formulas in intraocular lens power calculation of axial myopes undergoing cataract surgery - Sune, Pradeep; Sune, Mona; Mukherji, Ritica (Journal of Datta Meghe Institute of Medical Sciences University, 2021)
Context: Calculation of intraocular lens (IOL) power for extremes of axial lengths (ALs), using classical formulae like Sanders-Retzlaff-Kraff/Theoretical (SRK/T), is unsatisfactory. With the advent of fourth-generation formulae, surgeons are now aiming for better refractive outcomes for such patients postcataract extraction. Aims: The aim of this study was to assess and compare the accuracy of SRK/T, Holladay II, and Barrett Universal II formulae for IOL power calculation in high myopes with cataract by computing the mean absolute error (MAE). Settings and Design: This was a hospital-based prospective comparative study conducted over a period of 1 year. Forty patients with AL ≥26 mm undergoing cataract extraction were included after taking inclusion and exclusion criteria into consideration. Subjects and Methods: After enrolling patients and obtaining informed consent, all patients underwent a comprehensive ophthalmic examination. The power of IOL to be implanted was calculated by SRK/T, Holladay II, and Barrett Universal II with the goal of achieving refraction within ± 1 D postoperatively. Phacoemulsification was performed for all patients and hydrophilic foldable IOLs were implanted. Patients were followed up for 2 months at the end of which MAE was calculated for all three formulae. Statistical Analysis: Statistical analysis was done by descriptive and inferential statistics using Kruskal-Wallis Chi-square test and Mann-Whitney U-test. Software used in the analysis was SPSS 24 version and P < 0.5 was considered as the level of significance. Results: Barrett Universal II formula had the lowest MAE with a mean of 0.06 ± 0.20 and a median absolute error of 0.02. This was followed by Holladay II and SRK/T. While Barrett Universal II outperformed for all powers of IOL, SRK/T had lower MAE for plus power IOLs and Holladay II was better for negative-power IOLs. Conclusions: Barrett Universal II formula is ideal for IOL power calculation in cataract patients with AL >26 mm.